Trends in media framing of industrial crises reporting: implication for media research in Nigeria (2019)
There has been a scholarly argument among media researchers on how best media analysts should study media perspectives on industrial crisis reporting with reference to research methods, theoretical perspectives and methods of data analysis. Content analysis and meta-analytical approach were employed to gather data from published scholarly articles and theses accessed online. One hundred and fifteen (115) studies were content analyzed, collated and identified based on those that focused their issues on media framing of labour crisis. Evidence from the studies analysed shows that the content analysis and in-depth interviews were predominantly adopted for media representations of industrial crisis, the mixed method research were adopted for data collection while media framing, agenda setting and the priming theories were mostly adopted by most of the studies. It is recommended that studies should employ critical discourse analysis to compliment researchers’ effort to examine how different ideological stances are mediated in the media to reflect social-political dominance, inequality and class struggle that characterize industrial crisis.